Motivasi Belajar Mahasiswa Akuntansi Sebelum Dan Sesudah Menjadi Perguruan Tinggi Negeri (Studi Kasus Pada Mahasiswa Prodi Akuntansi Angkatan 2012 UPN “VETERAN” Jawa Timur): Learning Motivation of Accounting Students Before and After Becoming a State University (Case Study on Accounting Study Program Students Class of 2012 UPN "VETERAN" East Java) - Nuraini, Fitri (Journal of Accounting Science, 2017)
The Motivation has a strategic role in the activities of one's learning, no one is learning without motivation. Motivation to learn is the driving force of psychic overall in students that lead to learning and provides direction on learning activities in order to achieve a goal, the motivation also provide encouragement in learning so that students (Purba, 2012). UPN is a university that on October 6, 2014 has turned into State Universities (PTN). The change of State Universities (PTN) expected higher student motivation to learn is certainly offset by the factors that influence it so that it can create quality graduates other than Pioner Development skilled, reliable and professional in competition in the world of work. The population used was 200 students Prodi Accounting preferred class of 2012 students. The sampling technique using simple random sampling the formula Slovin at 67. The study used statistical test paired sample t-test. The results show that there are differences in learning motivation between before and after the college on students in the accounting department of UPN "Veteran" East Java. It is known that the t value obtained from processing the data is - 2.801 with siginifikansi level of 0,007 or less 0.05.